Gallic Acid Improved Amytryptiline Effect in Neuropathic Pain Induced by Partial Sciatic Nerve Ligation (PSNL) in Rats - Neerati, Prasad; Enumula, Vinay (Natural Products Journal, The, 2021)
Aim and Background: Amytriptiline (AMY), an antidepressant, is used in the treatment of neuropathic pain. However, with limited therapeutic benefits and side effects of AMY, it is not helpful to the majority of the neuropathic pain patients. Gallic acid (GA) is a polyphenolic product with potential antioxidant effects, useful in neuropathic pain. Objective: The purpose of the study was to investigate the improved neuropathic pain relief with GA in combination with AMY in rats. Methods: Partial sciatic nerve ligation (PSNL) method is used for neuropathic pain induction in rats. The rats were randomly divided into 6 groups (n = 8), and treated with drugs or vehicle once daily for 15 days after the pain induction. The first group served as Normal control and received normal saline (p.o), the second group served as Sham Control and received Normal Saline (p.o), the third group served as Surgery Control and received normal saline (p.o), the fourth group received AMY (25mg/kg, p.o), while the fifth group received GA (100mg/kg,p.o), and the sixth group received both AMY and GA. Further behavioural studies for pain were carried out on days 1,4,7,10,13,16,19 and 22. Histological studies of sciatic nerves were carried out on days 1, 15 and 22, and on the 22nd day, all the remaining animals were sacrificed for the biochemical estimations of the sciatic nerve tissues. Results: GA attenuates neuropathic pain better in combination with AMY by ameliorating the behavioral, biochemical and histopathological signs and symptoms. This resultant effect is due to its antioxidant, antinociceptive and anti-inflammatory actions. It also potentiates AMY antinociceptive and antioxidant effects when given in combination in a continuous treatment. Conclusion: The results suggest that GA in combination with AMYattenuated the neuropathic pain. Hence, the use of GA as an adjunctive with AMY in the neuropathic pain will be more therapeutically beneficial; further studies on patients to confirm the results are warranted.
Keywords: partial sciatic nerve ligation (PSNL)